1995
DOI: 10.3354/meps122147
|View full text |Cite
|
Sign up to set email alerts
|

Predatory and suspension feeding of the copepod Acartia tonsa in turbulent environments

Abstract: The copepod Acartia tonsa exhibits 2 different feeding modes: when feeding on small phytoplankton cells it sets up a feeding current and acts as a suspension feeder; when feeding on motile prey it acts as an ambush feeder. We examined experimentally the effects of small-scale turbulence on feeding rates in these 2 modes. The different feeding behaviours were triggered by offering the copepods diatoms Thalassiosira weissfloqii and ciliates Strombidium sulcatum, respectively. Turbulence at 5 different intensitie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
121
1

Year Published

2002
2002
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 188 publications
(130 citation statements)
references
References 13 publications
(27 reference statements)
8
121
1
Order By: Relevance
“…Numerous studies have shown that copepods respond remotely to potential mates , Weissburg et al 1998, predators (Drenner & McCormas 1980), and prey (Siaz & Kiørboe 1995, Jonsson & Tiselius 1990. Although the stimuli used to identify and locate other individuals may involve a cocktail of chemical and fluid mechanical signals, the results of previous studies have shown that mechanical signals are sufficient to elicit feeding (Yen & Fields unpubl.…”
Section: Introductionmentioning
confidence: 66%
“…Numerous studies have shown that copepods respond remotely to potential mates , Weissburg et al 1998, predators (Drenner & McCormas 1980), and prey (Siaz & Kiørboe 1995, Jonsson & Tiselius 1990. Although the stimuli used to identify and locate other individuals may involve a cocktail of chemical and fluid mechanical signals, the results of previous studies have shown that mechanical signals are sufficient to elicit feeding (Yen & Fields unpubl.…”
Section: Introductionmentioning
confidence: 66%
“…Saiz & Kiørboe 1995, Saiz et al 2003. In the present work, increasing turbulence decreased phytoplankton patchiness in inshore and offshore waters (see Figs.…”
Section: Small-scale Phytoplankton Patchiness and Zooplankton Grazingmentioning
confidence: 76%
“…This circumstance may shape many features of their physiological and morphological functioning including the efficiency of nutrient assimilation (1), prey-predator interactions (2) and cell division (3). One of the key controls turbulence exerts on phytoplankton results from its effect on sedimentation rates.…”
mentioning
confidence: 99%